Penyuluhan Penanganan Banjir untuk Mengukur Tingat Pengetahuan Siswa/i di MTsN 01 Kota Kendari - Siti Rabbani Karimuna; Andi Zakiah Aini Maftuha; Arzul Rahmat Asdar; Asnani Asnani; Bunga Lestari; Firda Julia; Karamoi Karamoi; Miftahul Hasanah; Mila Angraeni; Muh. Fitra Annaba; Nanda Visca Pradiny; Novi Damayanti; Wa Ratmi (Lembaga Pengembangan Kinerja Dosen, 2025)
In the last 20 years, Indonesia has experienced various natural disasters, especially floods, that threaten the lives of its citizens. This study aims to enhance community understanding of flood prevention through outreach activities in Manegen Village. The methods used include lectures, presentations, and leaflet distribution, conducted on May 26, 2025. The results indicate an increase in community knowledge about seasonal flood prevention. Additionally, this research highlights the importance of disaster education, environmental management, and emergency communication systems. This outreach program is designed to empower communities to be better prepared for disasters and provide education on post-flood health management.